1990
DOI: 10.1021/jf00098a007
|View full text |Cite
|
Sign up to set email alerts
|

Volatile constituents of essential oils obtained from newly developed tea tree (Melaleuca alternifolia) clones

Abstract: Volatile constituents of essential oils of eight different clones propagated from the Australian tea tree (Melaleuca alternifolia) were analyzed by gas chromatography and gas chromatography/mass spectrometry. The oils isolated by a simultaneous purging and solvent extraction method (SPE) contained high levels of monoterpenes, including -thujene, sabinene, a-terpinene, -terpinene, 1,8-cineole, terpinolene, and limonene. The volatile composition of oils prepared by a simultaneous steam distillation and solvent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…However, Garozzo et al used much longer exposure time periods (up to few days) at entirely different experimental conditions (no aerosol related experimental runs were undertaken). In addition, the oil composition varies from batch to batch and depends on growth conditions at the plantations (Kawakami et al 1990). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Garozzo et al used much longer exposure time periods (up to few days) at entirely different experimental conditions (no aerosol related experimental runs were undertaken). In addition, the oil composition varies from batch to batch and depends on growth conditions at the plantations (Kawakami et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was shown that essential oils are heterogeneous mixtures, with considerable batch to batch variation of constituents, depending on growth conditions at the plantations (Kawakami et al 1990;Moudachirou et al 1999). The antimicrobial activity of TTO is attributed mainly to terpinen-4-ol (35-45%) and 1,8-cineole (1-6%); however, other components such as a-terpineol, terpinolene, and a-and c-terpinene are also often present and potentially contribute to microbial disinfection (May et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The variation in composition of these, the two high terpinolene Californian clones (9) and eleven other unauthenticated cultivated or natural high terpinolene Melaleuca specimens is shown in Table 111. These high levels of terpinolene suggest that with the right choice of genetic material Melaleuca could be adapted to plantation situations for the production of terpinolene oils.…”
Section: Resultsmentioning
confidence: 99%
“…A preliminary report of the terpinolene-rich form of M. linarifolia by one of us (J. J.B.) has appeared (8) and two of several "M. alternqolia" clones cultivated in California have been reported (9) to contain higher than normal levels ofterpinolene.' The identity ofthe former source has been changed and that of the latter clones must remain unconfirmed as herbarium voucher material is not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…Classification and authentication of foods and quality of origin is an active area where multivariate statistical analysis of chemical data is used. Multivariate techniques such as principal components analysis has been used for analysis of chemical data for plant essential oils (Kawakami et al, 1990;Viljoen et al, 1995;Perry et al, 1996), food volatiles (Moshonas and Shaw, 1997), and for the sensory evaluations of food flavours (Stampanoni, 1993). Such analyses are used for discriminating between groups where there is high sample variability within a group.…”
Section: Multivariate Statistical Analysis Of Quantitative Chemical Dmentioning
confidence: 99%